eXtended new reality - Carvalho, Fausto de (2021)
This article addresses some aspects of the potential of Extended Reality (XR) technologies in the context of the accelerated ongoing digital transformation, with public awareness and wider acceptance being prompted by current pandemic, due to the widespread adoption of teleworking, distance learning, and virtual conferences. The state-of-the-art of XR technologies and immersive environments is briefly addressed from the perspective of their sustained adoption in multiple scenarios, including education and training, well-being and active aging, and business.